Official Labeling, Criminal Embeddedness, and Subsequent Delinquency. A Longitudinal Test of Labeling Theory - Bernburg, Jón Gunnar (Journal of research in crime and delinquency, 2006)
This article examines the short-term impact of formal criminal labeling on involvement in deviant social networks and increased likelihood of subsequent delinquency. According to labeling theory, formal criminal intervention should affect the individual's immediate social networks. In many cases, the stigma of the criminal status may increase the probability that the individual becomes involved in deviant social groups. The formal label may thus ultimately increase involvement in subsequent deviance. We use panel data of a sample of urban adolescents to examine whether involvement in deviant social groups mediates the relationship between juvenile justice intervention and subsequent delinquent behavior. Using measures from three successive points in time, the authors find that juvenile justice intervention positively affects subsequent involvement in serious delinquency through the medium of involvement in deviant social groups, namely, street gangs and delinquent peers. ABSTRACT FROM AUTHOR